PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT. BANK CENTRAL ASIA TBK CABANG GAJAH MADA-JAKARTA - Selvia Octavia Situmorang; Theobaldus Boro Tura (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine the effect of compensation and motivation on employee performance at PT. Bank Central Asia Tbk Gajah Mada-Jakarta Branch partially or simultaneously. The method used is quantitative. The sampling technique used saturated samples and the sample obtained in this study was 64 employees. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, coefficient analysis, coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of this research show that compensation (X1) has a significant effect on employee performance (Y) with the regression equation Y = 0.324 + 0.287 In X2, the value obtained for t calculated > t table, namely (7,045 > 1.998), thus the variables X1 and Which means that compensation and motivation variables simultaneously influence employee performance. Analysis of the coefficient of determination shows that 88.7% of the influence of compensation and motivation variables on employee performance, while the remaining 24.3% is influenced by other factors that are not in this study.